Methoden und Ergebnisse einer hydrogeographischen Landesaufnahme von Ostnigeria - Herrmann, Reimer (ERDKUNDE, 1968)
After a short introduction to the purpose of hydrogeography, research methods are described under the headings of surface hydrology, air photo interpretation, analysis of water-level readings and the calculation of the climatic waterbudget balance and humidity. On this base the hydrogeography of Eastern Nigeria is described with the aid of cartographic examples. A general survey is given, with a hydrographic map on 1 : 1 million scale, of a profile along 8° 30’ Longitude East. Certain hydrogeographic units are more closely examined, with the help of detailed hydro geographic maps. They are: a portion of the Enugu Scarplands, the area west of the Niger-Benue confluence, and the southeast Niger delta.